Analysis of high school student’s mental model on fungi: Representation of students' conceptions - Yanti Hamdiyati; Taufik Rahman; Sanchia Azaria Sulaeman (Universitas Negeri Jakarta, 2022)
Learning biology requires complete knowledge in understanding it, as well as in fungi. Lack of understanding of a concept, difficulty in finding relationships between concepts, and lack of teachers’ understanding are the main causes of misconceptions which can be represented through mental models. This study aims to analyze students' mental models of fungi through drawing and writing tests (DW), concept maps, interviews, and questionnaires. Using descriptive analysis, researchers use qualitative analysis and interpretation to support the quantitative results. A total of 30 students of grade 10 were given a test. The results showed that the level of students' mental models on the fungi structure was at the level of D3 W3 (46.43%) or wrong/irrelevant answers and fungi reproductive was the level of D3 W2 (17.85%) or partially correct drawing and irrelevant writing. On concept maps, as many as 60.71% of students were at emergent level and the other students were at the transitional level. Most of the answers in the interviews showed agreement with the results shown in the quantitative tests, while the questionnaires indicated the learning experiences and difficulties that students encountered in learning the functions. The conclusion of this study shows that the mental model of students on fungi is still not close to the mental model of experts.